Modern Financial Asset Pricing Theories (Economic journal of Lesya Ukrainka Volyn National University, 2015)
In the article it was considerd the meaning of the prices and the asset pricing. The author proposes the definition of the stock market price as the monetary expression of the stock value and the asset pricing as the process of price formation in the stock market. It was made the comparative analysis of the basic assumptions of the neoclassical asset pricing models.The paper presents the new theory of stock market asset pricing, which is based on a stochastic discounted factor. This model avoids such assumptions as the completeness of the market, the existence of the representative investor, the normal distribution of the returns, a quadratic utility function, a market equilibrium and fulfills of the all investor needs.The author concludes that pricing models are distinguished mainly by their assumptions and the use of a specific model depends on the purpose of the study
Keywords: asset pricing, static pricing theory, portfolio theory, the capital pricing model, the arbitrage theory, a stochastic discount factor approach to asset pricing